HIV among men who have sex with men in Malawi: elucidating HIV prevalence and correlates of infection to inform HIV prevention. Issue 4 (2nd December 2013) - Wirtz, Andrea L; Jumbe, Vincent; Trapence, Gift; Kamba, Dunker; Umar, Eric; Ketende, Sosthenes; Berry, Mark; Strömdahl, Susanne; Beyrer, Chris; Baral, Stefan D
Abstract : Introduction: There are limited data characterizing the burden of HIV among men who have sex with men (MSM) in Malawi. Epidemiologic research and access to HIV prevention, treatment and care services have been traditionally limited in Malawi by criminalization and stigmatization of same‐sex practices. To inform the development of a comprehensive HIV prevention intervention for Malawian MSM, we conducted a community‐led assessment of HIV prevalence and correlates of infection. Methods: From April 2011 to March 2012, 338 MSM were enrolled in a cross‐sectional study in Blantyre, Malawi. Participants were recruited by respondent‐driven sampling methods (RDS), reaching 19 waves. Trained staff administered the socio‐behavioural survey and HIV and syphilis voluntary counselling and testing. Results: Crude HIV and syphilis prevalence estimates were 15.4% (RDS‐weighted 12.5%, 95% confidence interval (CI): 7.3–17.8) and 5.3% (RDS‐weighted 4.4%, 95% CI: 3.1–7.6), respectively. Ninety per cent (90.4%, unweighted) of HIV infections were reported as being previously undiagnosed. Participants were predominantly gay‐identified (60.8%) or bisexually identified (36.3%); 50.7% reported recent concurrent relationships. Approximately half reported consistent condom use (always or almost always) with casual male partners, and proportions were relatively uniform across partner types and genders. The prevalence of perceived and experienced stigma exceeded 20% for almost all variables, 11.4% ever experienced physical violence and 7% were ever raped. Current age >25 years (RDS‐weighted adjusted odds ratio (AOR) 3.9, 95% CI: 1.2–12.7), single marital status (RDS‐weighted AOR: 0.3; 95% CI: 0.1–0.8) and age of first sex with a man <16 years (RDS‐weighted AOR: 4.3, 95% CI: 1.2–15.0) were independently associated with HIV infection. Conclusions: Results demonstrate that MSM represent an underserved, at‐risk population for HIV services in Malawi and merit comprehensive HIV prevention services. Results provide a number of priorities for research and prevention programmes for MSM, including providing access to and encouraging regular confidential HIV testing and counselling, and risk reduction counselling related to anal intercourse. Other targets include the provision of condoms and compatible lubricants, HIV prevention information, and HIV and sexually transmitted infection treatment and adherence support. Addressing multiple levels of HIV risk, including structural factors, may help to ensure that programmes have sufficient coverage to impact this HIV epidemic among MSM.